THE INFLUENCE OF TOURISM INFORMATION EXPOSURE ON COMMUNITY INVOLVEMENT IN PANGLIPURAN TOURISM VILLAGE - Laba, I Nengah; Semara, I Made Trisna; Pantiyasa, I Wayan; Tujungsari, Komang Ratih (Journal of Business on Hospitality and Tourism, 2019)
Sustainable tourism development is becoming an international commitment to ensure the sustainability development for social welfare. Bali has experienced significant development growth in the past 20 years. The growth of the tourism development directly led to the development of the tourism village in Bali. This cannot be separated due to the community involvement. One of the tourism villages that experienced significant growth and development in Bali is Panglipuran tourism village. This research was designed with the aim of identifying and analyzing the influence of tourism information exposure on Community Involvement. Closed questionnaire technique was used to collect the data with measurement scale using Likert scale. There were 100 respondents used in this research. SmartPLS software was used to analyze the data. The results obtained from the Path Coefficients table show X à Y values of 22,985, which means that tourism information exposure has a positive and significant effect on community involvement in the development of Panglipuran Tourism Village.